Antibody prevalence and factors associated with exposure to Orientia tsutsugamushi in different aboriginal subgroups in West Malaysia. - Sun Tee Tay; Hafizatul Anis Mohamed Zan; Yvonne A L Lim; Romano Ngui (Public Library of Science (PLoS), 2013)
BACKGROUND: Limited data is available on the current status of scrub typhus infection in the aboriginal population in Malaysia. This study was aimed to provide recent data on the degree of exposure of 280 individuals from seven aboriginal subgroups to Orientia tsutsugamushi (causative agent of scrub typhus) in West Malaysia. The environment, socioeconomic and behavioural risk factors associated with the disease were also investigated. METHODS/FINDINGS: The antibody prevalence to O. tsutsugamushi ranged from 0 to 36.4% in seven subgroups, with high prevalence rates noted in subgroups involved in agricultural activity and the lowest prevalence rates noted in subgroups whose main occupations were associated to fishing. Univariate analysis indicated populations with age above 18 years (OR = 1.15, 95% CI = 1.02-1.30, P = 0.015), working (OR = 1.99, 95% CI = 1.01-3.92, P = 0.044), working at agriculture area (OR = 1.18, 95% CI = 0.98-1.42, P = 0.031), receiving household income less than US$ 166.7 (RM500) per month (OR = 2.43, 95% CI = 1.16-5.11, P = 0.016) and having close contact with animal pets (OR = 4.06, 95% CI = 1.20-13.76, P = 0.016) are significantly associated with exposure to O. tsutsugamushi. Multivariate analysis confirms that participants who are above 18 years old, receiving household income less than US$ 166.7 (RM500) per month and having close contact with animal pets are 3.6 times (95% CI = 1.81-7.03, P<0.001), 1.3 times (95% CI = 1.14-1.64, P = 0.002) and 1.2 times (95% CI = 1.05-1.06, P = 0.006) more likely to have exposure to O. tsutsugamushi, respectively. CONCLUSION: The present study indicates that scrub typhus is still an important disease in the aboriginal population in Malaysia. Awareness about the disease and education on the preventive measures are important in reducing the risk of acquiring scrub typhus in the population studied.